Improving education quality, equity and access in Ethiopia: Findings from the Young Lives school component - Nega, A (Young Lives, 2012)
Education, particularly basic education, is key in terms of laying a solid foundation for healthy human development and is also strongly related to various social and economic benefits. Impressive and rapid primary enrolment increases have been achieved in Ethiopia, and policymakers are focused on quality improvements through the Education Sector Development Plan and the General Education Quality Improvement Programme. To help inform this policy environment, this brief presents findings from a school-based survey carried out as part of the Young Lives longitudinal study. The brief shows the ongoing powerful impacts of children's household circumstances on learning. Children from poorer backgrounds tend to enrol later, make slower progress and are more likely to drop out without completing schooling, illustrating the importance of school flexibility in supporting many children. The brief also looks at how teaching matters, exploring the relationship between the nature of the learning environment and children's achievements and finding positive links between teacher qualification levels and the education received by pupils.